+0  
 
0
85
3
avatar+79 

 

(please show all work this helps me understand how you got the answers, thank you!) 

 Apr 24, 2021
 #1
avatar+513 
+2

Given set of equations are 

           \(y=x^2-3x+4\)                       ...(1)

and     \(x+y=4\)     ⇒ \(y=4-x\)        ...(2)

 

From eq. (1) and (2)

∴ \(x^2-3x+4=4-x\)

   \(x^2-2x=0\)

   \(x(x-2)=0\)

   \(x=0\)  or  \(2\) 

 

For x=0 in eq (1)                     For x=2 in eq(1)

⇒ y = 4                                   ⇒ y = 2

 

∴ The solutions are (0,4) and (2,2). 

 

 

~Looking forward smiley

 Apr 24, 2021
 #2
avatar+79 
+1

As always, thank you~

Corduroy  Apr 24, 2021
 #3
avatar+513 
0

No prob! :)

amygdaleon305  Apr 24, 2021

0 Online Users